Impacto da criação dos bancos digitais na demanda por moeda no Brasil - Ribeiro, Bruno Vinicius Chrisostomo (2024)
In recent years, investments in technology have led to advancements in banking services, both in the digitization of traditional banks and in the emergence and adoption of digital banks, which have been gaining more ground in the Brazilian market. Observing the accelerated growth of this modality, this work aimed to evaluate the impacts on the demand for money in Brazil following the emergence of digital banks. To achieve this, we used an econometric methodology based on a set of monthly time series from January 2012 to December 2023. The results obtained from the model estimation corroborate the theoretical assertion that technological innovations implemented in Brazil in recent years have caused a decrease in the demand for money.